Афоризмы. Письмо к отцу. Письма: перевод с немецкого / Франц Кафка - Кафка Франц (Вершины. Коллекция, 2000)
Экземпляры: (20190523) / Инвентарный номер: / Цена: / Сис.шифр: 84(4Авс) / Авт.знак: К 30 / ББК: 84(4Авс)